Plenty of puppets to make - Supraner, Robyn (U. S. A : Troll Associates, 1981)
Instructions for making puppets from milk cartons, cereal boxes, paper plates, egg cartons, and other materials.
Keywords: Puppet making-Juvenile literature; Puppet making; Handicraft